2012
DOI: 10.1039/c1cc15681k
|View full text |Cite
|
Sign up to set email alerts
|

A novel “turn-on” fluorescent chemosensor for the selective detection ofAl3+ based on aggregation-induced emission

Abstract: A water-soluble, 'turn-on' fluorescent chemosensor based on aggregation-induced emission (AIE) has been developed. It exhibits rapid response, excellent selectivity, and sensitivity to Al(3+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
148
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 358 publications
(148 citation statements)
references
References 31 publications
0
148
0
Order By: Relevance
“…15,16 Among the AIE luminogens, tetraphenylethene (TPE) have been intensively investigated because of its facile synthesis, good photostability, and bright fluorescence emission. 12,14,17,18 The approach that introducing TPE moieties to conjugated polymer chain can thus be employed to design and synthesis AIE Additional Supporting Information may be found in the online version of this article. active conjugated polymers to solve the ACQ effect.…”
mentioning
confidence: 99%
“…15,16 Among the AIE luminogens, tetraphenylethene (TPE) have been intensively investigated because of its facile synthesis, good photostability, and bright fluorescence emission. 12,14,17,18 The approach that introducing TPE moieties to conjugated polymer chain can thus be employed to design and synthesis AIE Additional Supporting Information may be found in the online version of this article. active conjugated polymers to solve the ACQ effect.…”
mentioning
confidence: 99%
“…The detection limit estimated, based on the 3σ/slope, was 24 nM, (Fig. S7), which was about two order lower than the WHO guideline (7.41 μM) for Al 3 þ in the drinking water (Alstad et al, 2005;Han et al, 2012), and comparable to those of the Al 3 þ chemosensors reported to show the lowest Fig. 1.…”
Section: Fluorescence and Absorption Spectroscopic Studies Of 1 Towarmentioning
confidence: 70%
“…The decrease in PL intensity with increase in the THF content from 75 to 95% is probably due to the rapid agglomeration of the TPP-3COO À molecules in a random manner, which forms less emissive, 'redder,' amorphous powders [26,31,43]. Very different behavior was shown by TPP-COO À , the emission intensity of which remained at almost zero at 'low' THF volume fractions (<40%) and showed an increase only at much higher THF contents (>40%) [58]. The enhancement of luminescence in the presence of a nonsolvent resulted from the change of molecular form (the relative distance between the molecules and the geometry of compounds in the solution state) from a solution state in water to aggregated particles in H 2 O-THF mixtures.…”
Section: Luminescence Properties Of Triphenylpyrrole Derivatives In Tmentioning
confidence: 90%